2015
DOI: 10.1038/srep13241
|View full text |Cite
|
Sign up to set email alerts
|

OLA1 regulates protein synthesis and integrated stress response by inhibiting eIF2 ternary complex formation

Abstract: Translation is a fundamental cellular process, and its dysregulation can contribute to human diseases such as cancer. During translation initiation the eukaryotic initiation factor 2 (eIF2) forms a ternary complex (TC) with GTP and the initiator methionyl-tRNA (tRNAi), mediating ribosomal recruitment of tRNAi. Limiting TC availability is a central mechanism for triggering the integrated stress response (ISR), which suppresses global translation in response to various cellular stresses, but induces specific pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
104
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(107 citation statements)
references
References 48 publications
3
104
0
Order By: Relevance
“…Whereas most null mutations of the YchF homologue in yeasts are nonlethal (7), inactivation of TcYchF by RNA interference (RNAi) in trypanosomes (Trypanosoma cruzi) inhibited the protozoan's growth (4). We (6) and others (8) reported that OLA1 knockdown (KD) in human cells under normal culture conditions had, depending on the origin of the cell lines used, either a negative effect or no effect on cell proliferation. However, under multiple cellular stresses, including oxidative stress, OLA1 KD promoted cell survival (9) by "gating" ISR and the expression of downstream proapoptotic factors, such as CHOP (6).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Whereas most null mutations of the YchF homologue in yeasts are nonlethal (7), inactivation of TcYchF by RNA interference (RNAi) in trypanosomes (Trypanosoma cruzi) inhibited the protozoan's growth (4). We (6) and others (8) reported that OLA1 knockdown (KD) in human cells under normal culture conditions had, depending on the origin of the cell lines used, either a negative effect or no effect on cell proliferation. However, under multiple cellular stresses, including oxidative stress, OLA1 KD promoted cell survival (9) by "gating" ISR and the expression of downstream proapoptotic factors, such as CHOP (6).…”
mentioning
confidence: 99%
“…We (6) and others (8) reported that OLA1 knockdown (KD) in human cells under normal culture conditions had, depending on the origin of the cell lines used, either a negative effect or no effect on cell proliferation. However, under multiple cellular stresses, including oxidative stress, OLA1 KD promoted cell survival (9) by "gating" ISR and the expression of downstream proapoptotic factors, such as CHOP (6). These paradoxical findings suggest that OLA1 plays multiple roles in the regulation of cell proliferation and cell survival.…”
mentioning
confidence: 99%
See 3 more Smart Citations